Comprehensive Literacy Instruction within Classroom Contexts: Teachers' Perceptions of Best Practices for Literacy - Jennifer Manak; Chelsey Bahlmann Bollinger; Courtney Shimek; Jennifer Barrett-Tatum; Debra Wellman (Arizona State University, 2022)
This study illuminates the voices of literacy teachers. Findings from this study were based on a questionnaire about what teachers perceive as best practices in literacy instruction. We received 44 fully completed questionnaires. The 44 teacher respondents ranged from Pre-K through 6th grade with experience ranging from 1 to 20+ years of teaching. Teachers came from rural, suburban, and urban schools, with 40% of these teachers in Title I schools. More than 130 best practices in literacy instruction were identified by our teacher participants. Teachers' responses illustrated many of the components of comprehensive literacy instruction that covered a broad array of practices from the initiation of instruction through the assessment of student learning. Literacy teachers' responses were organized into three themes: Preparing for Instruction, Literacy Instruction, and Student Assessment and Differentiation.